Biologia reprodutiva de Astyanax scabripinnis paranae (Eigenmann) (Ostheichthyes, Characidae), do ribeirão das Marrecas, bacia do rio Tibagi, Paraná - Veregue,Angela Maria Louzada (2003)
Some aspects of the reproductive cycle of female "lambari", Astyanax scabripinnis paranae (Eigenmann, 1927) were studied. The specimens were collected in intervals of fifteen days, from September 1979, until November 1980, in the Marrecas creek (Irerê and Paiquerê districts), Londrina, Paraná, Brazil. The maturity scale was characterized in five stages: immature, maturation, spawning, spent, and resting, which was established by the gonad-somatic relation and the ovary morphology and microscopic aspects. The maturation curve and distribution of maturity stages show that the period of reproduction is very long; spawning extended from July to March. The gonad cycle is related to seasons: maturation occurs chiefly in the winter months, spawning specimens are found in spring and summer, and those in rest are frequent in autumn. In the first sexual maturation the medium length of females was 5.04 cm. Also was observed more males than females during all collecting periods.